AD, Volume 14, n° 2, 1989 - Full Issue - journal system, (Africa Development, 1989)
Table of Contents La Question démocratique dans le tiers monde contemporain Samir Amin .......................... 5 The Character of the State, Legitimacy Crisis and Social Mobilization in Africa: An Explanation of Form and Character Eghosa E. Osaghae ....................... 27 L'Afrique et la Déréglementation du Transport Aérien A. Cournanel .......................... 49 Development Research in Eastern and Southern Africa: Some Issues for the 1990s Paul B. Vitta .......................... 87 Review Article Contested Landscape of Fragmented Communities Fassil Demissie ....................... 101 Publications Received ................. 113